Of Monsters and Migrants: On the Loss of Sanctuaries in Literature as a Parable of Biopolitics in the Twentieth and Twenty-First Centuries - Arnds, Peter (Hungarian Journal of English and American Studies, 2020)
To understand the cultural predecessors to the dehumanizing metaphors found in current populist rhetoric, it is beneficial to revisit some of the literary uses of such metaphors in the context of migration, xenophobia, and the notion of sanctuary. By rereading Mary Shelley’s Frankenstein (1818), Victor Hugo’s The Hunchback of Notre Dame (1830), and Bram Stoker’s Dracula (1897) in light of these paradigms, the article explores the links between the monster and the city as sanctuary: while Mary Shelley’s novel shows us the classical scenario of the undesirable being banned from human community, Stoker’s vampire breaks into the sanctuary of both city and nation state, reflecting time-worn fears of invasion and contamination by the racial Other. Hugo demonstrates a third common form of undesirability within the sanctuary, calling into mind Foucault’s concept of inclusion within the city/nation state while also being excluded from it. This article bridges between these texts and prominent scenarios in the treatment of migrants today. (PA)